Ficus diamantina (Moraceae) a new species from high montane forests in north-east Brazil - Machado, Anderson F. P.; Queiroz, Luciano Paganucci De (Phytotaxa, 2017)
A new species of fig tree endemic to the Chapada Diamantina in the northeastern Brazilian state of Bahia, is described and illustrated. Ficus diamantina belongs to the Ficus sect. Americanae. The new species occurs sympatrically with Ficus clusiifolia and shows affinities with Ficus bahiensis from which it differs by the reddish color of young branches with epidermis flaking off, the tector and glandular trichomes on the lamina abaxial surface, the number of lateral veins, the divergence angle of basal pair of veins and the subsessile syconia. It occurs in high montane forests near Campos Rupestres (upland rocky fields) at altitudes up to 800 m.